Evaluation of efficiency of advanced oxidative process in degradation of 2-4 dichlorophenol employing UV-C radiation reator - Zaidan, Léa Elias Mendes Carneiro; Pinheiro, Rannuzya Brandão; Santana, Rayany Magali da Rocha; Charamba, Lívia Vieira Carlini; Napoleão, Daniella Carla; Silva, Valdinete Lins da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
The study accomplished to analyze, identify and quantify 2,4-dichlorophenol employing high efficiency chromatography with a previously validated analytical methodology. The validation was made by using some analytical parameters: linearity, precision, accuracy, quantification limit (LOQ) and detection limit (LOD). The analytical curve was linear for the studied range of concentration (10 up to 100 mg.L-1) presenting a linear regression coefficient (R2) above 0,99. Regarding the methodology accuracy, a repeatability analysis was performed by observing a coefficient of variance (CV) below 20% for each of the concentrations used. The LOD and LOQ were adequate for the analyzed compound, showing the values of 1.42 mg.L-1 and 4.30 mg.L-1, respectively. The tests to verify the accuracy, by the recovery method provided values above 79%, thus resulting in specific, sensitive, precise, linear and accurate methodology in the studied concentration range. In the advanced oxidative process UV/H2O2, the compound was degraded to 88.04% under the following experimental conditions: [H2O2] = 1016.0 mg∙L-1 in 120 minutes. Therefore, it can be affirmed that the treatment employed can be used as an alternative for industrial effluent treatment with phenolic compounds.